Image representative with holographic technique as an alternative reading method for dyslexic - Nik Aziz, Nik Nor Azidah; Anuar, Roslaili; Mohd Radzuan, Nurul Asyiqin; Wan Zakaria, Wan Zamani; Abdullah, Khairul Zikri (Research and Innovation Division, Universiti Teknologi MARA (UiTM) Selangor, 2025)
This research strives to address the unique obstacles experienced by dyslexic children in their reading process by proposing an alternate teaching method employing image representation with holographic techniques. Dyslexia, a condition marked by neurobiological impairments, frequently impedes an affected individual's ability to analyze the alphabet and efficiently process textual information, particularly in reading. Due to the unique educational requirements of dyslexic children, which diverge from those of typically developing children, there is a clear imperative for developing targeted instructional resources designed to address their specific impairments. Therefore, this study presents an alternate pedagogical methodology to assist children with dyslexia, acknowledging the pressing nature of the issue. The study employs a purposive sampling method to select participants from the Persatuan Dyslexia Malaysia (PDM) in the Klang Valley, Malaysia, focusing on children aged 6 to 9. Utilizing a descriptive research methodology, the study applies qualitative methodology to collect detailed insights. The methodology applied encompasses direct observations of children with dyslexia and interviews with the teachers actively engaged in their educational processes. The research results highlight the efficacy of a reading methodology that integrates image representation with holographic approaches, indicating that dyslexic children readily embrace this unique approach. Moreover, the findings of this study make a substantial contribution to the provision of dyslexic children with an educational experience that is both valuable and engaging while also being in line with current educational practices. Introducing this alternative reading method elicits enthusiasm among dyslexic children, cultivating a favorable disposition towards literacy within the educational setting. The holographic technique effectively attracts the attention of dyslexic children and offers a multisensory approach that caters to their distinct learning preferences. As a result, it is recommended that teachers who are responsible for instructing dyslexic children adapt their instructional approaches in order to address the distinct difficulties associated with dyslexia, hence fostering an inclusive and efficient educational setting. This study supports implementing innovative methods and highlights the significance of teacher training and knowledge in effectively integrating new approaches into conventional education. In summary, the research highlights the significance of considering the distinct requirements of children with dyslexia and adapting instructional approaches to optimize their educational encounters. The suggested alternative reading method, which integrates image representation and holographic approaches, presents itself as a potentially fruitful route for enhancing student involvement and enhancing reading proficiency in children with dyslexia. This study provides valuable contributions to the special education field and promotes a more inclusive and dynamic instructional approach for dyslexic children in the context of Malaysian education. It highlights the importance of ongoing exploration and integration of innovative techniques to enhance the learning experience of dyslexic children.